2017
DOI: 10.1371/journal.pone.0173057
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes of pre-exposure prophylaxis for HIV prevention among physicians in Guatemala: Implications for country-wide implementation

Abstract: IntroductionHIV continues to be a major health concern with approximately 2.1 million new infections occurring worldwide in 2015. In Central America, Guatemala had the highest incident number of HIV infections (3,700) in 2015. Antiretroviral pre-exposure prophylaxis (PrEP) was recently recommended by the World Health Organization (WHO) as an efficacious intervention to prevent HIV transmission. PrEP implementation efforts are underway in Guatemala and success will require providers that are knowledgeable and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
1
26
2
Order By: Relevance
“…Health care workers (86.6%) showed similar interest in PrEP as their counterparts from neighboring East-African countries [ 18 ], while members of the community from our study were more interested in PrEP compared to data reported from some other African countries (93.5% vs 61% respectively[ 20 ]. This variability probably reflects differences in community engagement in and education around HIV prevention tools and strategies.…”
Section: Discussionmentioning
confidence: 64%
“…Health care workers (86.6%) showed similar interest in PrEP as their counterparts from neighboring East-African countries [ 18 ], while members of the community from our study were more interested in PrEP compared to data reported from some other African countries (93.5% vs 61% respectively[ 20 ]. This variability probably reflects differences in community engagement in and education around HIV prevention tools and strategies.…”
Section: Discussionmentioning
confidence: 64%
“…Key structural factors included perceived staff attitudes, a lack of quality assurance, a lack of data protection and confidentiality, and cost [31,32,37,40,50,52]. Apart from addressing stigma and general competency to provide MSM with PrEP among healthcare providers in LMICwhich have been noted by others [83,84] our results suggest that strengthening health systems so as to assure universal provision of high-quality PrEP, while protecting the identities of MSM, will be critical. Strengthening drug regulation in middle-income countries has also been highlighted as essential by other authors [85].…”
Section: Discussionmentioning
confidence: 67%
“…Almost all data related to provider willingness to prescribe PrEP include concerns about risk compensation, that is, the possibility that PrEP users will increase their risk behavior after going on PrEP, undermining the potential benefit. In surveys of provider attitudes toward PrEP prescription across countries, risk compensation concerns remain paramount, 39,40 and are associated with both prescribing and referring patients for PrEP in primary care. 41 Data on the existence of risk compensation effects are equivocal.…”
Section: Risk Compensation Is a Red Herringmentioning
confidence: 99%